THE ROLE OF CIRCULATING IMMUNE COMPLEXES IN CHILDREN WITH EPIDERMOLYSIS BULLOSA - A.A. Ismailova; T.U. Aripova; I.U. Khamraeva; Sh.Z. Khabibullaev; S.A. Ubaydullaev (International Scientific and Current Research Conferences, 2025)
Systemic inflammation is considered a key factor in the immunopathogenesis of epidermolysis bullosa (EB); however, this has been described only in small and heterogeneous cohorts. The systemic nature of inflammation in EB has been confirmed by numerous studies. Circulating immune complexes (CICs) are antigen–antibody complexes that form in the bloodstream and circulate throughout the vascular system. It is known that CICs can activate the complement system, leading to the destruction of bacteria, viruses, and even host antigens. These complexes can also be phagocytosed by monocytes and macrophages, which are responsible for clearing CICs from the circulation. Based on this rationale, we analyzed serum CIC levels in children with EB to evaluate their concentrations and the inflammatory significance of these immunological markers.